Study on the deformation mechanism of overlying strata under steeply dipping coal mining conditions: a case study of Xinjiang, China - Qibo Song; Yiqing Lv; Kaixin Zhang (All Earth)
This paper uses discrete element numerical simulation to study goaf instability patterns during steeply inclined coal seam mining in a Xinjiang coal mine. The findings are as follows: 1) Steeply inclined coal seam extraction causes significant displacement of the goaf’s roof and floor, forming a ‘厂’ shaped feature that intensifies with mining progress; 2) In multi-coal seam mining, both lateral and vertical roof displacements increase stepwise with mining depth, eventually stabilising with maximum displacement shifting downstream; 3) Tangential stress in the upper rock mass exceeds compressive stress in the goaf, causing sliding, while compressive stress exceeding tangential stress leads to bending deformation in the lower rock mass, compressing unmined coal seams and protective pillars; 4) Disrupted overburden stress balance forms an asymmetric stress arch around the goaf; 5) Repeated mining processes result in significant asymmetry in surface vertical and horizontal displacements. These findings offer a theoretical basis for understanding instability mechanisms in steeply inclined coal seam mining, aiding safe mining practices.